Odpowiedzi

2010-01-24T12:39:08+01:00
A) -4(2x+0,5) = -8x - 2
b) -(x+7)(x-3) = -(x2 -3x + 7x - 21) = -(x2 + 4x - 21) = -x2 -4x +21
c) -(x+2)-2x(x-1/2) = -(x+2) - 2x2 + x = -x - 2 - 2x2 + x = -2x2 - 2
d) -3(1-2y)+1/2(6-12y) = -3 + 6y + 3 - 6y = 0
e) 1-(z+5)(z-1) = 1 - (z2 - z + 5z - 5) = 1 - z2 + z - 5z + 5 = -z2 - 4z + 6
2010-01-24T12:42:54+01:00
A) -4(2x+0,5)= -8x-2
b) -(x+7)(x-3)=-x²+3x+7x-21
c) -(x+2)-2x(x-1/2)= -(x+2) (-2x²+x)=2x³-x²-4x²+2x=2x³-5x²+2x
d) -3(1-2y)+1/2(6-12y)=(-3+6y)(3-6y)=-9+18y+18y-36y=-9
e) 1-(z+5)(z-1)=(-z-5)(z-1)=-z²+z-5z+5=-z²+5-4z